Japan in transition from Tokugawa to Meiji - Jansen, arius B. (Princeton University Press, 1986)
In this collection of seventeen essays, leading scholars address the question of what kind and what degree of change accompanied the political events known as the Meiji Restoration. The authors make use of quantitative data and recent Japanese scholarship to add substantially to the understanding of this major historical transition. This volume, with its essays of uniformly high quality, is essential reading for anyone with a scholarly interest in the Meiji Period.